Training and its Role in Combating Transnational Organized Crime - Boubaia, Kamel; Berrabah, Said (Journal of Legal Studies and Researches, 2021)
Most of the international and national documents related to the topic of organized crime have agreed to crystallize many measures prepared for the purpose of strengthening the capacity of the mandated agencies in the field of combating organized crime, among them the security and judicial apparatus, which has become the latter in light of the various transformations in its commission that constitute an obsession to address it, and to confront this The challenge It was necessary to prepare the necessary preparations for this, including work on training law enforcement officers, which is of great importance in facing these terribly raging crimes.